Simulated Impact of Glacial Runoff on CO2 Uptake in the Gulf of Alaska. Issue 2 (30th January 2018) - Pilcher, Darren J.; Siedlecki, Samantha A.; Hermann, Albert J.; Coyle, Kenneth O.; Mathis, Jeremy T.; Evans, Wiley
Abstract: The Gulf of Alaska (GOA) receives substantial summer freshwater runoff from glacial meltwater. The alkalinity of this runoff is highly dependent on the glacial source and can modify the coastal carbon cycle. We use a regional ocean biogeochemical model to simulate CO2 uptake in the GOA under different alkalinity‐loading scenarios. The GOA is identified as a current net sink of carbon, though low‐alkalinity tidewater glacial runoff suppresses summer coastal carbon uptake. Our model shows that increasing the alkalinity generates an increase in annual CO2 uptake of 1.9–2.7 TgC/yr. This transition is comparable to a projected change in glacial runoff composition (i.e., from tidewater to land‐terminating) due to continued climate warming. Our results demonstrate an important local carbon‐climate feedback that can significantly increase coastal carbon uptake via enhanced air‐sea exchange, with potential implications to the coastal ecosystems in glaciated areas around the world. Key Points: The Gulf of Alaska was a net carbon sink for 2009 Low alkalinity tidewater glacial runoff diminishes coastal carbon uptake in summer and fall A shift toward higher alkalinity due to increased land‐terminating glacial runoff increases carbon uptake by 1.9–2.7 TgC/yr